THE ROLE OF GREEN ACCOUNTING IN ACHIEVING SUSTAINABLE DEVELOPMENT AND REDUCING THE ENVIRONMENTAL IMPACT OF ORGANIZATIONS - Halah Nomas Othman (Scholars Digest Publishing, 2025)
Recent studies on environmental management and green supply chain management have discovered environmental motivations as one of the most important organizational performance drivers. They can be a combination of organizational incentives, stakeholder pressures, and ethical reasons. The aim of this study is to analyze environmental orientation and its influence upon financial performance with particular attention to green supplier management and relational capital influence. Statistical sampling comprised 392 managers and experts who were from publicly owned businesses, and random sampling helped to select them. In relation to purpose, this research lies within applied research, while with regards to data collection, this is descriptive-survey research with structural equation modeling to analyze data Results of hypothesis tests were that environmental orientation positively influences financial performance. Additionally, environmental orientation positively influences green supplier management. The research also discovered that green supplier management significantly positively influences financial performance. Finally, this moderating effect of relational capital on environmental sustainability orientation and financial performance relationship is valid. I.e., voluntary disclosures by companies with respect to social responsibility are compatible and complementary to mandatory disclosures such as financial performance.
Keywords: Green supplier management, relational capital, financial performance, environmental sustainability orientation.